Baseline characteristics of patients with heart failure with mildly reduced or preserved ejection fraction : The FINEARTS-HF trial - Solomon, Scott D. (John Wiley & Sons, 2025)
Aims: To describe the baseline characteristics of participants in the FINEARTS-HF trial, contextualized with prior trials including patients with heart failure (HF) with mildly reduced and preserved ejection fraction (HFmrEF/HFpEF). The FINEARTS-HF trial is comparing the effects of the non-steroidal mineralocorticoid receptor antagonist finerenone with placebo in reducing cardiovascular death and total worsening HF events in patients with HFmrEF/HFpEF.
Methods and results: Patients with symptomatic HF, left ventricular ejection fraction (LVEF) ≥40%, estimated glomerular filtration rate ≥ 25 ml/min/1.73 m2, elevated natriuretic peptide levels and evidence of structural heart disease were enrolled and randomized to finerenone titrated to a maximum of 40 mg once daily or matching placebo. We validly randomized 6001 patients to finerenone or placebo (mean age 72 ± 10 years, 46% women). The majority were New York Heart Association functional class II (69%). The baseline mean LVEF was 53 ± 8% (range 34-84%); 36% of participants had a LVEF <50% and 64% had a LVEF ≥50%. The median N-terminal pro-B-type natriuretic peptide (NT-proBNP) was 1041 (interquartile range 449-1946) pg/ml. A total of 1219 (20%) patients were enrolled during or within 7 days of a worsening HF event, and 3247 (54%) patients were enrolled within 3 months of a worsening HF event. Compared with prior large-scale HFmrEF/HFpEF trials, FINEARTS-HF participants were more likely to have recent (within 6 months) HF hospitalization and greater symptoms and functional limitations. Further, concomitant medications included a larger percentage of sodium-glucose cotransporter 2 inhibitors and angiotensin receptor-neprilysin inhibitors than previous trials.
Conclusions: FINEARTS-HF has enrolled a broad range of high-risk patients with HFmrEF and HFpEF. The trial will determine the safety and efficacy of finerenone in this population.